On the determinants of bargaining-free membership in German Employers' Associations - Uwe Jirjahn (Industrial Relations Journal, 2022)
In~the 1990s, German employers' associations started offering bargaining-free membership. Firms can be members without the obligation to adhere to a collective agreement. This study examines the characteristics of firms choosing a bargaining-free membership. It shows the influence of works councils, union density, foreign ownership, firm size and firm age.
Keywords: 330